EVALUASI STRATEGI BERSAING PT AXIS TELEKOM INDONESIA DALAM INDUSTRI TELEKOMUNIKASI SELULAR - , Adri Febrianto ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The growth of telecomunication industry appeared since the 90âs and in 2001, PT. AXIS Telekom Indonesia (AXIS) has joined the industry with support from Saudi Telecom and MAXIS Malaysia. Knowing there are several new players in the industry, the big players such as Telkomsel, XL and Indosat keep strengthen their marketing strategy. In 2008-2009 was the example of tight competition amongst the telecomunication companies in term of their marketing strategy, at that time was known as the âprice warâ era. To make sure the longevity of AXIS in this tight competitive telecommunication industry, AXIS has to pay attention to the changes in the environment both external and internal environment. This research aims to perform the analysis on the external environment and internal PT. AXIS Telekom Indonesia (AXIS) that affect the company's main activities, namely mobile telecommunication services. Analysis of the external environment through the Five Forces Model, it is known that the attractiveness of this industry is high. This is because the intensity of competition in this industry is quite strong, so the bargaining power of suppliers is still high and the bargaining power of buyers in the medium to high category. Threats to the new competitors are still quite low considering the capital investment to start business in this industry is quite large and the threat of substitute products are very low because many regions in Indonesia that has not been reached by the infrastructure other than mobile telecommunications service. Thus, AXIS has to be more diligent in focusing the potential consumers with a proper segmentation and always keep update its service and innovation to give the best offers to the consumers. Methods of research using methods such as analysis of external Five Forces Model, Driving Forces and Key Success Factor in telecommuniaction mobile services industry, which aims to analyze how high is the attractive level for this industry, the factors that play a role in this industry and the key to success in this industry. In addition to internal analysis conducted has it company that aims to get the strength and weaknesses of the company can continue to compete and exist in this industry and implementation strategy that will be used by AXIS in the face of such change. Results of this analysis concluded that the best strategy for AXIS in the conditions of competition at this time is the Focused Strategy differentiation. Management of AXIS must implement this strategy in order to get the right target market and giving the service that needed by its consumers to make sure the existence in the telecommunications service, especially mobile telecommunication service industry.